Multimedia in the informed consent process for endoscopic sinus surgery: A randomized control trial. (30th November 2015) - Siu, Jennifer M.; Rotenberg, Brian W.; Franklin, Jason H.; Sowerby, Leigh J
Abstract : Objectives/Hypothesis: To determine patient recall of specific risks associated with endoscopic sinus surgery and whether an adjunct multimedia education module is an effective patient tool in enhancing the standard informed consent process. Study Design: Prospective, randomized, controlled trial. Methods: Fifty consecutive adult patients scheduled for endoscopic sinus surgery at a rhinology clinic of a tertiary care hospital were recruited for this study. Informed consent was studied by comparing the number of risks recalled when patients had a verbal discussion in conjunction with a 6‐minute interactive module or the verbal discussion alone. Early recall was measured immediately following the informed consent process, and delayed recall was measured 3 to 4 weeks after patient preference details were also collected. Results: Early risk recall in the multimedia group was significantly higher than the control group ( P = .0036); however, there was no difference between the groups in delayed risk recall. Seventy‐six percent of participants expressed interest in viewing the multimedia module if available online between the preoperative and procedural day. Sixty‐eight percent of patients preferred having the multimedia module as an adjunct to the informed consent process as opposed to the multimedia consent process alone. Conclusions: There is an early improvement in overall risk recall in patients who complete an interactive multimedia module, with a clear patient preference for this method. Here we emphasize the well‐known challenges of patient education and demonstrate the effectiveness of integrating technology into clinical practice in order to enhance the informed consent process. Level of Evidence: 1b Laryngoscope, 126:1273–1278, 2016